r(*) = r*
pls tell the difference between above two
Can you please give any source which contain r(*)=r*.Previous year question book gave answer b
and their b is (r*s*)*=(r+s)*
search question no (XVII)
(r*s*)*=(r+s)* but in case of (r*s*) != (r+s)*
**** Disclaimer : I am not sure that its right or wrong . So if its wrong please don`t blame me :P
I think r(∗) != r∗ ,
let take a example A(B*) . In this case (B*) will be evaluated first because its with in the bracket . And now consider this R(*) then (*) will be evaluated first but it contain only ∅ and ∅*= ∈ . So R.(∈) = R . peace
@Amitabh Tiwari 1 @Arjun Sir, here in this question mentioned in link https://gateoverflow.in/83956/gate-1992-which-following-regular-expression-identities-true
r(*)=r* is false, but in this question it's true. So, what is it True or False?
In this question , it is r(*)=r* and in your given link r(*)=r*
moreover , here option B) is (r*S*) = (r + s)* .. there option B) is (r*S*)* = (r + s)* ..
as you know (r*S*) != (r + s)* and other options also false so option A is chosen here.
These 2 questions are Not same ..option B is different
see this is 1992 paper, #xvii see here
and option A) here r(*) = r
option B, C and D all are false here .
https://gateoverflow.in/83956/gate-1992-2-xii As per this question option 1 is false. Please clarify.
On a lighter ...